Low Albumin to Fibrinogen Ratio Predicts Poor Overall Survival in Esophageal Small Cell Carcinoma Patients: A Retrospective Study - Wang Y; Li J; Chang S; Zhou K; Che G (Cancer Management and Research, 2020)
Yan Wang,* Jialong Li,* Shuai Chang, Kun Zhou, Guowei Che Department of Thoracic Surgery, West China Hospital, Sichuan University, Chengdu 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guowei Che Email cheguowei_hx@aliyun.comPurpose: To explore the prognostic value of albumin to fibrinogen ratio (AFR) in patients with esophageal small cell carcinoma (ESCC).Patients and Methods: Patients diagnosed with ESCC in West China Hospital from June 1, 2010, to July 31, 2019, were retrospectively reviewed. The AFR was defined as the ratio between the serum albumin level and fibrinogen level. The receiver operating characteristic curves were conducted to determine optimal cut-off values for survival prediction. Univariate and multivariate cox regression analyses were performed to clarify independent prognostic risk factors.Results: A total of 88 ESCC patients were enrolled in our study with the median follow-up time of 6 months (range 1– 91 months). In the univariate analysis, the node metastasis, extraesophageal metastasis status, tumor-node-metastasis (TNM) stage and AFR were found to be potentially related with overall survival (OS) of ESCC patients. After the multivariate analysis, AFR [hazard ratio (HR)=3.487, 95% confidence interval (CI): 1.179– 10.312; P=0.024] and TNM stage (HR=6.044, 95% CI: 1.045– 34.974; P=0.045) were testified to be independent prognostic factors and low AFR (≤ 12.36) level was significantly associated with poor OS in ESCC patients.Conclusion: The current study reported that AFR could serve as a novel prognostic indicator in ESCC and patients with AFR≤ 12.36 were more likely to have poor prognosis.Keywords: albumin to fibrinogen ratio, esophageal small cell carcinoma, overall survival